Testing for Lupus Anticoagulants - Moore, Gary W. (Seminars in Thrombosis and Hemostasis, 2022)
Lupus anticoagulant (LA) is one of the three criteria antiphospholipid antibodies (aPLs) employed in classification, and by default diagnosis, of antiphospholipid syndrome (APS). Detection of LA is not via calibrated assays but is based on functional behavior of the antibodies in a medley of coagulation assays. A prolonged clotting time in a screening test is followed by demonstration of phospholipid dependence and inhibitory properties in confirmatory and mixing tests, respectively, which are modifications of the parent screening test. Complications arise because no single screening test is sensitive to every LA, and no test is specific for LA, because they are prone to interference by other causes of elevated clotting times. Several screening tests are available but the pairing of dilute Russell's viper venom time (dRVVT) with LA-sensitive activated partial thromboplastin time (aPTT) is widely used and recommended because it is proven to have good detection rates. Nonetheless, judicious use of other assays can improve diagnostic performance, such as dilute prothrombin time to find LA unreactive with dRVVT and aPTT, and the recently validated Taipan snake venom time with ecarin time confirmatory test that are unaffected by vitamin K antagonist and direct factor Xa inhibitor anticoagulation. Expert body guidelines and their updates have improved harmonization of laboratory practices, although some issues continue to attract debate, such as the place of mixing tests in the medley hierarchy, and areas of data manipulation such as assay cut-offs and ratio generation. This article reviews current practices and challenges in the laboratory detection of LA.
Keywords: activated partial thromboplastin time; antiphospholipid syndrome; antiphospholipid antibodies; dilute prothrombin time; dilute Russell's viper venom time; lupus anticoagulant; Taipan snake venom time